The Impact of Handwashing Education through Animation Videos on Knowledge and Attitudes towards Handwashing among UMY Students during the COVID-19 Pandemic - Kusbaryanto Kusbaryanto; Istianadea Putri Rahmadani (Research Synergy Foundation, 2023)
In this study, the primary objective was to assess the impact of teaching about hand washing and video animation on the knowledge and attitudes of UMY students regarding hand washing during the Covid-19 pandemic. A one-group pre-posttest design was used, involving 63 student respondents selected through simple random sampling. Data was collected using a questionnaire, and the findings revealed a significant increase in both knowledge (p = 0.031) and attitudes (p = 0.040) towards hand washing. The study emphasizes the importance of educating students about hand washing practices, as it is expected to benefit them in their future roles in healthcare institutions, contributing to improved infection prevention and control measures. It is worth noting that this study focused solely on knowledge and attitudes towards hand washing and did not assess actual hand washing compliance.